(untitled) (International Journal of Business, Economics and Management, 2018)
This study examined how effective implantation of social protection programmes in the agricultural sector will induce youth participation, thereby creating employment for the youths and reduce the incidence of households’ poverty in Nigeria. The study engaged a qualitative discuss methodology from the Living Standard Measurement Study-Integrated Households Panel Survey on agriculture for two farming seasons (post-planting and post-harvest seasons). Results showed that, out of the three main activities (agricultural, non-farm enterprise and wage employment) engaged by the Nigerian households, for the post-planting interview, agriculture remains the most engaged activity, this is because; about 38.5% of the rural households engaged in agriculture; 17.9% engaged in nonfarm enterprise, while 7.8% engaged in wage employment. It was also noted that; more of the women engaged in a household-nonfarm activities (25%) than men; however, fewer youths engaged in both agriculture (21.8%) in the post-planting visit. The farmers revealed that, one of the reasons for less youth participation in the agricultural activities is due to the low attractiveness of the sector to the youths. Therefore, the study recommended that the agricultural activities should be made attractive through the implementation of social protection programmes to induce youth participation as this will boost rural opportunities and reduce the rural-urban migration and its attendant challenges.